The Stability of Economics Integration and Endogenous Growth - Michael B. Devereux; Beverly J. Lapham (Queen's University, Department of Economics, 1993)
This paper examines the transitional dynamics of economic integration in the two country endogenous growth model of Rivera-Batiz and Romer (1991) and in an extension by Rivera-Batiz and Xie (1992). It is shown that, in the absence of knowledge flows across countries economic integration will generically lead to a corner solution where only one country does all the R&D and the other specializes in manufactures. When countries are symmetric the world growth rate in this equilibrium will always be higher than in autarky. When countries differ in their human capital endowment, the world growth rate with trade is always greater than the autarky growth rate of the "low-growth"country, but may or may not be greater than the autarky growth rate of the "high-growth" country.
Keywords: 330